Wedelolactone, an Anti-inflammatory Botanical, Interrupts c-Myc Oncogenic Signaling and Synergizes with Enzalutamide to Induce Apoptosis in Prostate Cancer Cells - Sarveswaran, Sivalokanathan; Ghosh, Ritisha; Parikh, Rujul; Ghosh, Jagadananda (Molecular cancer therapeutics, 2016)
The c-Myc gene encodes an oncoprotein transcription factor that is frequently upregulated in almost all cancer types and is the subject of intense investigation for management of cancer because of its pleiotropic effects controlling a spectrum of cellular functions. However, due of its nonenzymatic nature, development of suitable strategies to block its protein–protein or protein–DNA interaction is challenging. Thus, c-Myc has been recognized as an elusive molecular target for cancer control, and various approaches are in development to inhibit c-Myc transcriptional activity. We observed that wedelolactone (WDL), an anti-inflammatory botanical compound, severely downregulates the expression of c-Myc mRNA in prostate cancer cells. Moreover, WDL dramatically decreases the protein level, nuclear accumulation, DNA-binding, and transcriptional activities of c-Myc. c-Myc is a transforming oncogene widely expressed in prostate cancer cells and is critical for maintaining their transformed phenotype. Interestingly, WDL was found to strongly affect the viability of Myc-activated prostate cancer cells and completely block their invasion as well as soft agar colony formation in vitro. WDL was also found to downregulate c-Myc in vivo in nude mice xenografts. Moreover, WDL synergizes with enzalutamide to decrease the viability of androgen-sensitive prostate cancer cells via induction of apoptosis. These findings reveal a novel anticancer mechanism of the natural compound WDL, and suggest that the oncogenic function of c-Myc in prostate cancer cells can be effectively downregulated by WDL for the development of a new therapeutic strategy against Myc-driven prostate cancer. Mol Cancer Ther; 15(11); 2791–801. ©2016 AACR.